MPS.BR nível G: obtenção de qualidade em desenvolvimento de software - Gass, Silvane (2011)
This paper presents a study on the MPS.BR (Brazilian Software Process Improvement), with emphasis on how a company that wishes to obtain MPS.BR level G certification must proceed toward this goal. This study was based in part on experience gained with the implementation of the model in a software company in the west of Paraná.